Human Serum Proteins and Susceptibility of Acinetobacter baumannii to Cefiderocol: Role of Iron Transport - Le, Casin (2022)
Cefiderocol, a recently introduced antibiotic, has a chemical structure that includes a cephalosporin that targets cell wall synthesis and a chlorocatechol siderophore moiety that facilitates cell penetration by active iron transporters. Analysis of the effect that human serum, human serum albumin, and human pleural fluid had on growing Acinetobacter baumannii showed that genes related to iron uptake were down-regulated. At the same time, β-lactamase genes were expressed at higher levels. The minimum inhibitory concentrations of this antimicrobial in A. baumannii cells growing in the presence of human serum, human serum albumin, or human pleural fluid were higher than those measured when these fluids were absent from the culture medium. These results correlate with increased expression levels of β-lactamase genes and the down-regulation of iron uptake-related genes in cultures containing human serum, human serum albumin, or human pleural fluid. These modifications in gene expression could explain the less-than-ideal clinical response observed in patients with pulmonary or bloodstream A. baumannii infections. The exposure of the infecting cells to the host’s fluids could cause reduced cefiderocol transport capabilities and increased resistance to β-lactams. The regulation of genes that could impact the A. baumannii susceptibility to cefiderocol, or other antibacterials, is an understudied phenomenon that merits further investigation.